Investigation on the Applications of Ethernet VPN in Cloud Data Center Interconnection - Xiaoming He; Hong Tang; Zhihua Liu; Yongbing Fan (Dianxin kexue)
The problems existing in the current VPLS services and new requirements for ethernet VPN are summarized,and the technical characteristics of E-VPN and PBB E-VPN newly presented by IETF are introduced and analyzed.Furthermore,integrated with the actual application requirements of the cloud data center interconnection,the applications of ethernet VPN in cloud data center interconnection are investigated.